APLIKASI VIDEO KLIP DENGAN RUBRIK PENILAIAN TERHADAP PENINGKATAN KETERAMPILAN PROSES PADA PEMBELAJARAN MICRO TEACHING MAHASISWA PROGRAM STUDI BIOLOGI - Abdul Rauf (Fakultas Keguruan dan Ilmu Pendidikan, 2018)
The type of this research is an experimental study with the application of video clips with assessment articles on micro teaching courses as an effort to provide experience to student participants to be able to master teaching skills to enter teaching reel in the implementation of field experience programs (PPL) in various schools. The training method used is to carry out the micro-learning process through taking pictures directly to each individual and then evaluating skills and acting through rubric process skills. The results of the evaluation of the implementation are given in percent. If the participant has not reached a minimum assessment standard of 85%, it must be repeated until it reaches that standard. Achievement of values ​​obtained through the application of video clips and rubric assessment of process skills will be compared with other students who micro-learning does not use both of these things. Comparison of observations on the mastery of process skills from the two student groups is the basis of calculations in drawing conclusions.